Distribution of HPV infection and tumour markers in cervical intraepithelial neoplasia from cone biopsies of Mozambican women. Issue 1 (27th December 2004) - Carrilho, C; Cirnes, L; Alberto, M; Buane, L; Mendes, N; David, L
Abstract : Aims: To evaluate human papillomavirus (HPV) infection in whole cervical cone specimens with cervical intraepithelial neoplasia (CIN). In addition, to evaluate the relation between the presence of CIN lesions and HPV infection and the expression of Ki-67, p53, cytokeratins, Gp230 glycoprotein, and simple mucin-type carbohydrates. Methods: Cervical cone specimens from five patients with CIN were studied. For each specimen, serial sections encompassing the whole cone were collected (52 samples). HPV infection and HPV types were detected by the polymerase chain reaction and enzyme immunoassay. The expression of Ki-67, p53, cytokeratins, Gp230, and simple mucin-type carbohydrates was examined immunohistochemically. Results: All cases showed high risk HPV types, namely types 16, 33, 35, and 58. Four of the five patients were infected by multiple viral types. HPV-58 was always seen in CIN III, whereas HPV-35 was more frequent in CIN I. The expression of Ki-67 and p53 was higher in CIN III lesions. The expression of cytokeratins 8 and 17 showed complete or almost complete overlap with CIN III. Altered expression of Gp230, Tn, and sialyl-T was often seen in all grades of CIN. Conclusions: When whole cervical cone specimens are evaluated the rate of multiple HPV infection is very high. The expression of cytokeratins 8 and 17 is a useful marker of CIN III.